Kebijakan Pemerintah dalam Memberikan Insentif Pajak Penghasilan Pasal 21 Kepada Wajib Pajak Terdampak Pandemi Covid-19 - I Putu Widya Laksana Pendit; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Jurnal Konstruksi Hukum, 2021)
The Covid-19 pandemic has been going on since the end of 2019 and has had a huge impact in the health, social and economic recession in Indonesia. The Government needs to take policies to anticipate these problems through fiscal policy. One of the policies issued was the provision of income tax incentives article 21 to affected workers. The problems of this research cover the substance of government policies in providing income tax incentives article 21, and the impact of providing income tax incentives article 21 for workers. The research method used is a normative legal research method, with a statutory and conceptual approach to the problem. The technique of collecting legal materials is carried out by recording, identifying, inventorying, and compiling according to the types of available legal materials. Based on the research results, it was found that the provision of Article 21 income tax incentives and borne by the Government has specific requirements regarding the business category and the amount of salary of workers who have the right to get the incentives. This is regulated in the Minister of Finance Regulation and implementation instructions through a letter from the Directorate General of Taxes Number SE-47/PJ/2020. The impact of providing this incentive can increase workers' income because income tax of Article 21 is borne by the government and helps workers maintain purchasing power. Thus, it can be concluded that the provision of income tax article 21 which is borne by the government has a fairly good impact on workers who meet the criteria and requirements, so that workers can also get incentives that are appropriate to their work and are able to support their daily needs.